Analisis Miskonsepsi Pada Materi Biimplikasi Dalam Pembelajaran Logika Matematika - Nofa Nasywa Ramadhani; Erlanda Samuel Purba; Hiyoshi Friyona Silalahi; Ester Fransiska Nababan; Sergi Br Sembiring; Wingston Leonard Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Textbooks are one of the reading resources used by prospective educators and educators as teaching materials to understand a subject before it is taught. This study aims to analyze the forms of misconceptions in the material of biimplication in mathematical logic learning, specifically in textbooks used as learning resources for students and university students. The background of this research is based on the fact that mathematical logic is a very important foundation of deductive thinking in learning, yet many difficulties in understanding and conceptual errors are still found among students and university students. The study used a descriptive qualitative approach with a content analysis method on three mathematics textbooks: Mathematics for Elementary School Teacher Education (2011), Logic & Set Theory (2010), and Mathematics for Senior High School Grade X (2006). Data were collected through a documentary study by examining definitions, truth tables, notations, and example problems related to biimplication. The results of the analysis indicate three categories of misconceptions: conceptual, procedural, and representational.